Influence of Heating ПГУ–КЭС Scheme Parameters with Additional Fuel Combustion on Changes in Plant Heat Efficiency - L. Tarasevich; A. Tuzankin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains an analysis pertaining to the influence of heating ПГУ–КЭС scheme parameters on changes in heat efficiency during additional combustion of fuel in a waste-heat boiler.